2019
DOI: 10.1016/j.neo.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Inflammation-Associated CXCL8-CXCR1 Signaling Inhibits Tumorigenicity Initiated by Sporadic- and Colitis-Colon Cancer Stem Cells

Abstract: Dysfunctional inflammatory pathways are associated with an increased risk of cancer, including colorectal cancer. We have previously identified and enriched for a self-renewing, colon cancer stem cell (CCSC) subpopulation in primary sporadic colorectal cancers (CRC) and a related subpopulation in ulcerative colitis (UC) patients defined by the stem cell marker, aldehyde dehydrogenase (ALDH). Subsequent work demonstrated that CCSC-initiated tumors are dependent on the inflammatory chemokine, CXCL8, a known indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…RPS6KB1 and CREB1 expression were positively correlated with that of CXCL8, whereas there was an inverse correlation between BAD and CXCL8 expression. Our findings were consistent with the existed evidence indicating that the genes that mediate cell proliferation and differentiation were upregulated while proapoptotic genes were downregulated during tumor progression (Xiao et al, 2015;Fisher et al, 2019). These results suggest that CXCL8 may regulate the expression of RPS6KB1 and CREB1 to promote cell proliferation and differentiation while inhibiting BAD expression to suppress apoptosis of CRC cells.…”
Section: Rps6kb1supporting
confidence: 92%
“…RPS6KB1 and CREB1 expression were positively correlated with that of CXCL8, whereas there was an inverse correlation between BAD and CXCL8 expression. Our findings were consistent with the existed evidence indicating that the genes that mediate cell proliferation and differentiation were upregulated while proapoptotic genes were downregulated during tumor progression (Xiao et al, 2015;Fisher et al, 2019). These results suggest that CXCL8 may regulate the expression of RPS6KB1 and CREB1 to promote cell proliferation and differentiation while inhibiting BAD expression to suppress apoptosis of CRC cells.…”
Section: Rps6kb1supporting
confidence: 92%
“…CXCL8 and its receptors are involved not only in mediating interactions between tumor cells and stromal cells but also in regulating the tumor microenvironment in primary CRC as well as its liver metastasis and promoting colorectal cancer progression by inducing angiogenesis, regulating tumor-associated stroma, or acting directly on tumor cells. Numerous clinical studies, including our research, have demonstrated that the elevated levels of CXCL8 in serum and tissues from colorectal cancer patients were related to the grade, stage, lymph node metastasis, and liver metastasis of CRC ( P < 0.05), while the survival curve analysis also showed that the significantly decreased disease-free survival (DFS) and overall survival (OS) ( P < 0.05) were highly related to the high expression of CXCL8 in CRC patients, which led to tumor progression and a poor prognosis [22, 35, 54, 55].…”
Section: Cxcl8 and Its Receptors In The Growth And Progression Of mentioning
confidence: 99%
“…In a subsequent and very recent paper, the authors demonstrated that in vitro CRCSC respond to IL-8-dependent proliferation in a dose-dependent manner and knock down either IL-8 or CXCR1 results in dysregulation of cell cycle progression (cyclin D1 and B1), consequent proliferation arrest and angiogenesis inhibition. Similar results were also obtained in in vivo xenograft mice [69] .…”
Section: Il-8 Involvement In Crc Stem Cellssupporting
confidence: 86%